ChemInform Abstract: Detection and Electronic Structure of Naked Actinide Complexes: Rhombic‐Ring (AnN)2 Molecules Stabilized by Delocalized π‐Bonding. Issue 22 (12th May 2016) - Vlaisavljevich, Bess; Andrews, Lester; Wang, Xuefeng; Gong, Yu; Kushto, Gary P.; Bursten, Bruce E.
Abstract: Linear NUN dinitride molecules (isoelectronic with the uranyl dication) and minor amounts of UN are obtained in matrix isolation experiments from laser ablated and excited (microwave discharge) U atoms and N2 in excess Ar or N2 at 4 or 7 K.